Studi Komparatif Penyediaan Penerjemah Terhadap Penghadap Notaris Tuli Di Indonesia Dan Jepang - Muhammad Reza Hastomo Aji (Universitas Islam Indonesia, 2020)
This study aims to compare the Law on Notary Office in Indonesia (UUJN) with the Law on Notary Office in Japan (Koshoninho) in the case that the Notary finds deaf people/communities as their clients, with the first problem formulation, what are the differences between UUJN and Koshoninho in providing translators for deaf applicants? Second, how do notaries in Indonesia implement UUJN when they find deaf applicants as their clients ? This is a normative juridical research in which interviewing the informants become additional information in this study. The results of the research conclude that, first, the differences in the provision of translators for deaf Notaries on UUJN and Koshoninho are in the condition of applicants, the use of translator phrases, and recognition of deaf people/communities, second, the implementation of a Notary in Indonesia when they find deaf people as clients is by using the services of a sign language interpreter.